Traveling Planetary Waves in Ozone Layer over Antarctic Peninsula - Grytsai, A.V.; Grytsai, Z.I.; Evtushevsky, A.M.; Milinevsky, G.P.; Leonov, N.A. (Національний антарктичний науковий центр МОН України, 2004)
Preliminary results of the analysis of the traveling planetary wave evolution in the ozone layer over the region of Antarctic Peninsula are presented. Total ozone data obtained at the Vernadsky station and TOMS satellite measurements are used. The main characteristics of the traveling waves, namely the spectral distribution, period, amplitude and velocity were considered. At the station latitude of 65.25°S the amplitude of the traveling wave number 2 becomes equal or exceeds the stationary wave number 1 amplitude in individual cases only. In average for the period 1979-2003 the relationship of amplitudes of the wave numbers 1, 2, 3, 4 and 5 is 1, 0.56, 0.29, 0.19, and 0.15. The wave periods 6-8 and 10-12 days are dominant. Velocities of 8-10 m/s are obtained. Наводяться попередні результати аналізу еволюції біжучих планетарних хвиль над регіоном Антарктичного півострова. Використано дані вимірювань загального вмісту озону в атмосфері на станції Академік Вернадський та супутникових вимірювань TOMS. Розглянуто основні характеристики біжучих хвиль, зокрема, спектральний розподіл, періоди, амплітуда і швидкість. На широті станції 65.25°S амплітуда біжучих хвиль з хвильовим числом 2 буває близькою або перевищує амплітуду стаціонарної хвилі 1 лише в окремих випадках. Амплітуди хвильових чисел 1, 2, 3, 4 та 5 в середньому за період 1979-2003 рр. співідносяться як 1, 0.56, 0.29, 0.19 та 0.15. Переважають періоди хвиль 6-8 та 10-12 днів. Швидкості одержано в межах 8-10 м/с.